Experimental study and mesoscale finite element modeling of elastic modulus and flexural creep of steel fiber-reinforced mortar. (11th January 2023) - Liang, Siming; Du, He; Liu, Yuhang; Chen, Yuxuan; Liu, Jiankun; Wei, Ya
Highlights: Effect of steel fiber content and curing age on mortar creep was assessed by a flexural test. A mesoscale FE model was developed for creep prediction of fiber-reinforced mortar. Effect of steel fiber orientation on mortar creep was quantified numerically. Abstract: Incorporation of fiber into cementitious materials would affect their mechanical and creep properties. The macro creep test is normally time-consuming and is difficult to evaluate the influence of the microstructures fully. This study investigated experimentally the elastic modulus and flexural creep of mortars with different volume fractions of steel fibers. Then a mesoscale finite element (FE) model consisting of mortar and randomly-distributed steel fibers was developed. The results show that the elastic modulus of mortars increases with increasing volume fraction of steel fiber, but the specific flexural creep exhibits an opposite trend. The influence of volume fraction of steel fiber on the specific flexural creep is more significant than that on the elastic modulus. The mesoscale FE model developed in this study is capable of capturing well the development of elastic modulus and flexural creep of mortars with different volume fractions of steel fibers. The simulated results reveal that fiber orientation is an important factor affecting the elastic modulus and flexural creep of steel fiber-reinforced mortars. The flexural creep (elastic modulus) of steel fiber-reinforced mortar increases (decreases) with increasing fiber rotational angle with respect to the stress direction. Moreover, both the elastic modulus and flexural creep of the mortar containing randomly-distributed steel fibers are equivalent to those of the mortars with steel fibers distributed by a fixed rotational angle of 30° when the volume fraction of steel fiber ranges from 1% to 3%. The findings in this study are expected to provide references to further investigations of elastic and creep properties of fiber-reinforced cementitious materials.